NHC-catalyzed enantioselective synthesis of tetracyclic δ-lactones by (4+2) annulation of ortho-quinodimethanes with activated ketones - Sarkar, Deeptanu; Barik, Shilpa; Shee, Sayan; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic Letters, 2023)
The N-heterocyclic carbene (NHC)-catalyzed generation of ortho-quinodimethanes (o-QDMs) from 9H-fluorene-1-carbaldehydes followed by the interception with activated ketones resulting in the enantioselective synthesis of tetracyclic delta-lactones is presented. High diastereoselectivity of products, remote C-(sp(3))-H functionalization, broad substrate scope, and mild reaction conditions are the notable features of the present (4 + 2) annulation.